The Effectiveness of using the Whatshapp Application as a Medium of Communication for Da'wah - Dasa Syawal Syahputra (UIN Salatiga, 2022)
Abstract The purpose of this study is to describe the effectiveness of using the Whatsapp application as a medium for proselytizing communication within the As-Sunnah Deli Serdang Islamic College of North Sumatra and find out the advantages obtained by application users to spread proselytizing messages while knowing what obstacles are often faced by application users in utilizing the Whatsapp application as a medium of da'wah communication. Based on the research conducted, the results were obtained that the use of the Whatsaap Application as a medium for proselytizing communication carried out by educators and education staff of the As-Sunnah Islamic College was less effective, it happened because of the lack of feedback obtained when sending proselytizing messages and some obstacles experienced by application users.